HOW IS THE DISTRICT HEALTH CENTER IMPROVING THE QUALITY OF HEALTH SERVICES IN THE KAMPAR KIRI TENGAH SUBDISTRICT? - Utama, Putri; Hastuti, Weni Puji (Universitas Negeri Yogyakarta, 2023)
This research was conducted at the Kampar Kiri Tengah District Health Center, Kampar Regency. This research aims to determine the community health center's strategy for improving the quality of health services in the Kampar Kiri Tengah sub-district. Data was processed using qualitative descriptive methods. Data was obtained through direct observation, documentation, and interviews, where the respondents' answers were described and then analyzed by the author. In this research, the community health center's strategy for improving the quality of health services in the Kampar Kiri Tengah sub-district is seen based on the 2020 Strategic Plan (BLUD) of the UPTD Kampar Kiri Tengah Community Health Center, Kampar District Health Service regarding Program Strategy, Funding, Indicators, and Targets. From the results of program measurements for each indicator, the strategy for improving the quality of health services in the Kampar Kiri Tengah sub-district can be good. Efforts made by community health centers include establishing family health service programs, nutrition improvement programs, infectious disease eradication programs, environmental health programs, and health promotion efforts where the program aims to improve public health and provide good services